Social nation how to harness the power of social media to attract customers, motivate employees, and grow your business - Libert, Barry (John Wiley & Sons, 2010)
It's time to join Social Nation and prosper!This book will show you, as an employee, customer or partner, how to use new social technologies, make yourself heard, and produce better products and services. As a leader and manager, you'll find out how to use these tools to harness social interactions to improve your business and to create your own social nation. The book provides a social assessment for leaders, managers and employees to scientifically evaluate your individual social skills and competencies. This book relies on well-known case studies about businesses that illustrate how social p.